2010
DOI: 10.1111/j.1600-0501.2010.01946.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagen membranes at immediate implants: a histomorphometric study in dogs

Abstract: The use of collagen-resorbable membranes at implants immediately placed into extraction sockets contributed to a partial (23%) preservation of the buccal outline of the alveolar process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 31 publications
2
62
0
5
Order By: Relevance
“…Caneva et al evaluated the use of a collagen membrane over the buccal gap of immediately placed implants and found that the alveolar crest outline was better maintained at the test sites compared with the control sites even if the buccal gap was relatively small [98]. Interestingly, enhanced bone preservation was found when using deproteinized bovine bone mineral particles and a collagen membrane compared to controls whereas no such benefit was noted when using magnesium-enriched hydroxyapatite [99101].…”
Section: Rationale For Extraction Socket Preservationmentioning
confidence: 99%
“…Caneva et al evaluated the use of a collagen membrane over the buccal gap of immediately placed implants and found that the alveolar crest outline was better maintained at the test sites compared with the control sites even if the buccal gap was relatively small [98]. Interestingly, enhanced bone preservation was found when using deproteinized bovine bone mineral particles and a collagen membrane compared to controls whereas no such benefit was noted when using magnesium-enriched hydroxyapatite [99101].…”
Section: Rationale For Extraction Socket Preservationmentioning
confidence: 99%
“…The implant should not touch the buccal plate of the socket wall in the maxillary anterior teeth, because such touching could cause resorption of buccal plate and esthetic risk. [71][72][73] The implant must be placed at least 1 mm subcrestally, especially if the buccal or lingual plates are thin, 63 or 2 to 3 mm below the gingival margin. 74 The extraction and the placement of the implant should be flapless, when possible, 62 or can use a sulcular incision, 1 tooth mesial and 1 tooth distal to the implant site, which could help to expose the buccal bone.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Para tanto, diferentes materiais de enxerto, incluindo enxerto ósseo autógeno, alógeno, xenógeno e sintéticos, associados ou não ao uso de membranas, vêm sendo utilizados em uma tentativa de preservar o rebordo alveolar após exodontia [9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Introductionunclassified
“…It has been suggested that the immediate placement of an implant in the fresh extraction socket could reduce alveolar ridge resorption following tooth removal [5][6][7][8][9] , however, localized osseous defects around immediate implants may present a challenge to the clinician 3,4,10,11 .…”
Section: Introductionmentioning
confidence: 99%